2023
DOI: 10.1001/jamanetworkopen.2023.4149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disulfiram and Copper Plus Chemotherapy vs Chemotherapy Alone on Survival in Patients With Recurrent Glioblastoma

Abstract: ImportanceDisulfiram has demonstrated broad antitumoral effect in several preclinical studies. One of the proposed indications is for the treatment of glioblastoma.ObjectiveTo evaluate the efficacy and safety of disulfiram and copper as add-on to alkylating chemotherapy in patients with recurrent glioblastoma.Design, Setting, and ParticipantsThis was a multicenter, open-label, randomized phase II/III clinical trial with parallel group design. Patients were recruited at 7 study sites in Sweden and 2 sites in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 57 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…Unfortunately, few clinical trials of DSF have achieved the expected results owing to the inefficient delivery of DSF and Cu 2+ to tumor sites and small sample sizes. For example, a phase II/III clinical trial found that among patients with recurrent glioblastoma, DSF combined with temozolomide led to significantly increased toxic effects but no significant difference in survival, compared with chemotherapy alone, suggesting that DSF and copper did not benefit patients with recurrent glioblastoma ( Werlenius et al, 2023 ). Taken together, these findings suggest that altering the intracellular copper concentration could be a promising therapeutic strategy for a subset of tumors.…”
Section: Therapeutic Strategies For Targeting Copper In Cancermentioning
confidence: 99%
“…Unfortunately, few clinical trials of DSF have achieved the expected results owing to the inefficient delivery of DSF and Cu 2+ to tumor sites and small sample sizes. For example, a phase II/III clinical trial found that among patients with recurrent glioblastoma, DSF combined with temozolomide led to significantly increased toxic effects but no significant difference in survival, compared with chemotherapy alone, suggesting that DSF and copper did not benefit patients with recurrent glioblastoma ( Werlenius et al, 2023 ). Taken together, these findings suggest that altering the intracellular copper concentration could be a promising therapeutic strategy for a subset of tumors.…”
Section: Therapeutic Strategies For Targeting Copper In Cancermentioning
confidence: 99%
“…Copper-ionophores have been clinically tested as anticancer agents, such as clioquinol 14 and disulfiram. 15 By chelating extracellularly and releasing Cu(II) under the reductive intracellular environment, 16,17 copper-ionophores exhibit a complex anticancer mechanism, including generating reactive oxygen species (ROS) and inducing cellular oxidative stress, 18 inhibiting proteasomal activity, 19 enhancing the clearance of Xlinked inhibitor of apoptosis protein (XIAP). 20 Elesclomol (ES), developed by Synta Pharmaceuticals, has achieved the furthest advance in clinical trials among these copper-ionophores.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This study registered with ClinicaTrials.gov (NCT03034135) across multiple institutions demonstrated that DSF/Cu treatment exhibits minimal efficacy in treating IDH-wild type glioblastoma patients without selection and seemingly fails to enhance sensitivity to temozolomide significantly [ 248 ]. Another clinical trial (NCT02678975) also indicated that combining disulfiram and copper with standard chemotherapy for the treatment of recurrent glioblastoma did not lead to an increase in patient survival rates [ 249 ]. Moreover, a daily treatment with a 400 mg dose of disulfiram was associated with a higher incidence of adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a daily treatment with a 400 mg dose of disulfiram was associated with a higher incidence of adverse effects. Consequently, the study concluded that this combination therapy does not confer an advantage for patients with recurrent glioblastoma [ 249 ].…”
Section: Introductionmentioning
confidence: 99%